New geophysical constraints on a failed subduction initiation: The structure and potential evolution of the Gagua Ridge and Huatung Basin. (6th February 2015) - Eakin, Daniel H.; McIntosh, Kirk D.; Van Avendonk, H. J. A.; Lavier, Luc
Abstract We modeled the velocity structure of the Huatung Basin and Gagua Ridge using offshore wide‐angle seismic data along four ∼E‐W transects. These transects are accompanied by several multichannel seismic reflection (MCS) profiles that highlight the shallow deformation in this area east of Taiwan. Although it is agreed that the Gagua Ridge was the product of a transient compressional episode in the past, relatively few data have been collected that reveal the deeper structure resulting from this enigmatic process. The velocity models show evidence for normal, to thin, oceanic crustal thicknesses in the Huatung Basin and West Philippine Basin. Moho reflections from the associated MCS profiles confirm the thickness observed in the velocity models. The velocity models indicate significant crustal thickening associated with the Gagua Ridge, to 12–18 km along its entire length. Most importantly, the two central velocity models also show a significant asymmetry in the crustal thickening, suggesting a westward underthrusting of >20 km of WPB oceanic crust beneath that of the Huatung Basin. This geometry is extremely unexpected given interpretations that indicate the Huatung Basin could be significantly older than the West Philippine Basin (Early Cretaceous versus Eocene). Our observations, along with recent geophysical data concerning the age of the Huatung Basin, indicate that the Gagua Ridge was the result of a failed subduction event during the Miocene that may have existed simultaneously and for a short time, competed with the Manila subduction zone to the west in accommodating convergence between the Eurasia and Philippine Sea plates. In this scenario, the present‐day Gagua Ridge represents a snapshot of a failed subduction initiation preserved in the geologic record.